DEVELOPMENT OF TRANSDERMAL DOSAGE FORM USING COPROCESSED EXCIPIENTS OF XANTHAN GUM AND CROSS-LINKED AMYLOSE: IN VITRO AND IN VIVO STUDIES - SURINI, SILVIA; SICILIA, ASTINA; SOFIANI, RIKA; KHOIRIAH, SITI; INDRIATIN, UFAIRAH H.; SARI, SANTI PURNA; HARAHAP, YAHDIANA (International Journal of Applied Pharmaceutics, 2020)
Objective: A transdermal hydrogel dosage form consists of a three-dimensional polymer network that binds water in large quantities and is used for drug delivery. The study’s aim was to prepare coprocessed excipients as a matrix for a transdermal hydrogel containing diclofenac sodium and examine in vitro and in vivo drug penetrations. Methods: Four types of coprocessed excipients were produced using two methods that combined crosslinking and coprocessing steps. The produced excipients were formulated as transdermal gels containing sodium diclofenac. An in vitro penetration test was then performed using a Franz diffusion cell to pass the drug through a rat skin membrane. An in vivo penetration test was performed by applying the hydrogel to the abdominal skin of male Sprague-Dawley rats and then measuring the plasma drug concentration. Results: In vitro penetration results showed that the flux from Co-CLA6-XG 1:2, Co-CLA12-XG 1:2, CL6-Co-A-XG 1:2, and CL12-Co-A-XG 1:2 transdermal hydrogels was 655.23±116.43 μg∙cm−2/h, 569.08±26.58 μg∙cm−2/h, 867.42±101.27 μg∙cm−2/h−1, and 736.99±15.39 μg∙cm−2/h−1. The in vivo study resulted in area under the curve for the Co−CLA6−XG 1:2, Co−CLA12−XG 1:2, CL6−Co−A−XG 1:2, and CL12−Co−A−XG 1:2 transdermal hydrogels was 32.08±5.40 μg∙ml−1∙h, 34.27±8.34 μg/ml∙h, 6.20±2.90 μg/ml∙h, and 14.38±2.38 μg/mL∙h, respectively. Conclusion: The study results showed that the excipients could be processed to form a matrix within a transdermal hydrogel formulation and deliver sodium diclofenac into systemic circulation in a controlled release manner.